N. Saad, and V. Kadirkamanathan. “A DES approach for the analysis and modeling of supply chain system for instability analysis”. Simulation Modeling Practice and Theory, Volume 14, Issue 5, July 2006, pp 541-563. - Saad , Nordin; kadirkamanathan, V (Elsevier, 2006)
In this paper, a modeling and simulation approach for the analysis of a supply chain system taking into account the relations of the system to its contextual components is presented. The purpose is to address several issues particularly on whether decision policies would provide stability in the presence of disturbances, as well as evaluating the effect of disturbances on the system. The task of developing a contextual load model requires the identification of the possible sources of disturbances that exist in the system, the modeling of these disturbances and the particular parameters in the model that are to be changed to simulate such disturbances. Results revealed the robustness of the various decision policies to the different types of disturbances. In particular, it was seen that pseudo PID, a policy derived from the control system view point, exhibited much more robustness than other policies.